A knowledge-based, structural-aided discovery of a novel class of 2-phenylimidazo[1, 2-a]pyridine-6-carboxamide H-PGDS inhibitors. (1st September 2021) - Schulte, Christie A.; Deaton, David N.; Diaz, Elsie; Do, Young; Gampe, Robert T.; Guss, Jeffrey H.; Hancock, Ashley P.; Hobbs, Heather; Hodgson, Simon T.; Holt, Jason; Jeune, Michael R.; Kahler, Kirsten M.; et al.
Graphical abstract: Through an internal virtual screen performed at GlaxoSmithKline a distinct class of 2-phenylimidazo[1, 2-a]pyridine-6-carboxamide H-PGDS inhibitors were discovered. Careful evaluation of crystal structures and SAR led to a novel, potent, and orally active imidazopyridine inhibitor of H-PGDS, 20b . Herein, describes the identification of 2 classes of inhibitors, their syntheses, and their challenges. Abstract: Through an internal virtual screen at GlaxoSmithKline a distinct class of 2-phenylimidazo[1, 2-a]pyridine-6-carboxamide H-PGDS inhibitors were discovered. Careful evaluation of crystal structures and SAR led to a novel, potent, and orally active imidazopyridine inhibitor of H-PGDS, 20b . Herein, describes the identification of 2 classes of inhibitors, their syntheses, and their challenges.